PWE-041 Ibd – the unseen effects of chronic illness. (22nd June 2015) - Beaton, FM; Paterson, JC; Robinson, E; Todd, JA; Reynolds, N; Mowat, C; Groome, M
Abstract : Introduction: Inflammatory Bowel Disease (IBD), incorporating Crohns Disease (CD) and Ulcerative colits (UC), is a chronic condition that can cause significant gastrointestinal morbidity. Alongside the anticipated gastrointestinal symptoms, patients with chronic illness may experience issues with low mood, relationships, employment and education opportunities, and may miss significant time off work. In this pilot project, we sought to record the additional morbidity experienced by a typical cohort of IBD patients. Method: Over a 3-week period 100 consecutive patients attending an IBD clinic in a tertiary teaching hospital were surveyed by questionnaire. Questions addressed demographics, impact of IBD on lifestyle, mood, relationships, and education/employment. Disease activity over the preceding 12 months was noted. Remission was defined by Physician Global Assessment, plus the absence of steroid use within the last 12 months, plus normal CRP. Data were analysed according to disease activity. Results: A total of 100 questionnaires were completed by 44 males (aged 15–80) and 56 females (aged 19–81). 63 patients had CD (M:F 28:35), 37 had UC (M:F 16:21). 56% of patients had clinically active disease and 44% were in clinical remission. There was no significant difference in ages between those patients with active or inactive disease. The majority in both groups had felt depressed at times; 81% of those patients with active disease and 68% with inactive disease. Table 1 shows morbidity by disease activity. 75% from each group reported IBD has impacted on their lifestyle in the preceding 12 months, and over 60% from each group reported IBD had restricted their activities. In terms of employment, 3% were unemployed with active disease and 16% in the inactive group with the rest being in some form of employment, full time education or retired. Only 32% of those with active disease and 31% in remission reported no loss of days at work in the preceding 12 months. 16% of those with active disease and interesting 36% of those in remission reported the loss of greater than 2 weeks at work due to their IBD in the preceding 12 months. Conclusion: We have demonstrated that, irrespective of disease activity, IBD has a significant impact on the physical and psychological health, and employment record of the patients surveyed. Patients' psychological health is important and should be actively addressed when reviewing patients with IBD in outpatient clinics. Disclosure of interest: None Declared.